Reasons for appealing against resolutions of the supervisory boards in companies – a comparative analysis of Sawed corporate acts in the light of the Code of Commercial Companies and the Civil Code - Glinka, Justyna (Studia Iuridica Toruniensia, 2017)
Within the subject of appealing against resolutions adopted by the supervisory boards there are many issues that require clariWcation. Apart from arguments in favour of applying either the provisions on challenging the shareholders’ resolutions accordingly or general provisions of the Civil Code, it is worth analysing potential defects of corporate acts which can be the cause to undermine their validity in legal and economic turnover. Presentation of the discrepancy between the scope and the eYects of the application of art. 58 of the Civil Code and factors determining appropriate legal action on the basis of Code of Commercial Companies not only enriches the debate in terms of challenging the decisions of the managing authorities, but above all allows the abstract assessment of how far reaches the principle of limited autonomy of the company law.